2021
DOI: 10.1111/joop.12338
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to support autonomy, competence, and relatedness needs in organizations: A systematic review with recommendations for research and practice

Abstract: Organizational research underpinned by self‐determination theory (SDT) has grown substantially over the past decade. However, the effectiveness of interventions designed to promote support for basic psychological needs in organizations remains ill documented. We thus report the results of a qualitative systematic review and synthesis of SDT‐informed studies of interventions to cultivate autonomy, competence, and relatedness needs, and in turn, autonomous motivation in organizational contexts. Studies were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 79 publications
1
50
0
3
Order By: Relevance
“…As previously stated, need satisfaction can be improved through need support, which has been shown in numerous studies (see Slemp et al, 2021 for a review). Need support entails different components, but there is no consensus on which components should be involved (Rocchi et al, 2017).…”
Section: Basic Psychological Needsmentioning
confidence: 89%
See 1 more Smart Citation
“…As previously stated, need satisfaction can be improved through need support, which has been shown in numerous studies (see Slemp et al, 2021 for a review). Need support entails different components, but there is no consensus on which components should be involved (Rocchi et al, 2017).…”
Section: Basic Psychological Needsmentioning
confidence: 89%
“…SDT is an evidence‐based theory that, when applied in an organizational setting, allows us to have a positive impact on workers' attitudes and behaviours. It also proposes a well‐validated model for what to do to advance and sustain motivation and engagement (Hardré & Reeve, 2009; Slemp et al, 2021). For example, many well‐validated metrics of the motivational and emotional components that influence outcomes such as engagement were used in this intervention study.…”
Section: Theoretical Background and State Of Researchmentioning
confidence: 99%
“…For example, to support workers' basic needs, managers focused on nurturing workers' inner motivational resources, and provided an explanatory rationale for requests (Hardré & Reeve, 2009;Jungert et al, 2021). Recent meta-analyses and review research has also confirmed that need-supportive behaviors at the workplace were effective in increasing workers' intrinsic motivation, performance, and job-related behaviors (Cerasoli et al, 2016;Slemp et al, 2021;Van den Broeck et al, 2016).…”
Section: Social and Hierarchical Relationships To Satisfy Basic Psych...mentioning
confidence: 99%
“…Avey et al (2011) showed that when leaders enact the features of psychological capital (i.e., hope, optimism, resilience, and selfesteem), follower positivity and performance were enhanced. However, a potential risk of interventions targeting leaders is that changes in leader behavior do not always trickle down to the subordinate level (Slemp et al, 2021). (Garcea et al, 2009).…”
Section: Targeting Individualsmentioning
confidence: 99%